2010-2015 yılları arasında Türkiye-Katar ticari ilişkileri ekonomi-politik analizi - Yılmazbilen, Yeliz (My University, 2019)
Basra Körfezinde bulunan Katar, 1871 yılından Dünya Savaşına kadar Osmanlı Devleti’nin kazası olmuştur. Ekonomisi inci ticaretine bağlı olan Katar, doğalgazın keşfiyle dünyada enerji gücü haline gelmiştir. Doğalgazın sıvılaştırılarak ticaretinde dünyada birinci sırada olan Katar, kişi başına düşen milli gelirle ise ikinci sıradadır. GSYH’nın yaklaşık yüzde ellisini oluşturan doğalgaz, Katar’ın ekonomisini belirlemektedir. 2001 yılı sonrası Türkiye’nin Ortadoğu ile artan ticari politik ilişkileri Katar ile de yaşanmıştır. Türkiye’nin artan doğalgaz ihtiyacı, Katar’ında dünya doğalgaz ihracında ilk sırada gelmesi iki ülke arasındaki ilişkinin değerlendirilmesini gerekli kılmıştır.

Qatar located in Persian Gulf had been the village of Ottaman Empire from 1871 to the World War.Qatar became the energy power of the World by discovering the natural gas which the economy is determined by the pearl trade. Qatar is at the first rank at he World for tranporting the natural gas via liquefaction, and at the second rank in terms of national income per individual. The natural gas which shares the 50% of the GDP is determining the Qatar’s economy. The polite and commercial relationship between Turkey and Middle East after 2001, has also been realized with Qatar as well. As Qatar is at the first rank for exporting the natural gas and the increasing need of Turkey to natural gas, required a discussion of the relationships between two countries
Keywords: Basra Körfezi; Katar; Middle East; Ortadoğu Turkey; Persian Gulf; Qatar; Türkiye